Functions of regulators of G protein signaling 16 in immunity, inflammation, and other diseases - Tian, Miaomiao; Ma, Yan; Li, Tao; Wu, Nijin; Li, Jiaqi; Jia, Huimin; Yan, Meizhu; Wang, Wenwen; Bian, Hongjun; Tan, Xu; Qi, Jianni (Frontiers in Molecular Biosciences, 2022)
Regulators of G protein signaling (RGS) act as GTPase activating proteins to accelerate GTP hydrolysis of the G protein α subunit, leading to the termination of the G protein-coupled receptor (GPCR) downstream signaling pathway. RGS16, which is expressed in many cells and tissues, belongs to one of the small B/R4 subfamily of RGS proteins and consists of a conserved RGS structural domain with short, disordered amino- and carboxy-terminal extensions and an α-helix that classically binds and de-activates heterotrimeric G proteins. But with the deepening of research, it was found that RGS16 protein not only regulates the GPCR classical pathway, but also affects immune, inflammatory, tumor and metabolic processes through non-classical pathways such as MAPK, PI3K/Akt, RhoA and SDF-1/CXCR4. Currently, we also found that RGS16 protein may be involved in HBV-induced inflammatory response. Therefore, given that the continuous expansion of its role and mechanism, we will review the structure, characteristics, regulatory mechanisms and known functions of the small RGS protein-RGS16 in this paper to prepare for diagnosis, treatment and prognostic evaluation of different diseases such as immunity, inflammation, tumor and metabolic disorders and to better study its function in other diseases.